Design of orthogonal genetic switches based on a crosstalk map of σs, anti‐σs, and promoters. Issue 1 (29th October 2013) - Rhodius, Virgil A; Segall‐Shapiro, Thomas H; Sharon, Brian D; Ghodasara, Amar; Orlova, Ekaterina; Tabakh, Hannah; Burkhardt, David H; Clancy, Kevin; Peterson, Todd C; Gross, Carol A; Voigt, Christopher A
Abstract : Cells react to their environment through gene regulatory networks. Network integrity requires minimization of undesired crosstalk between their biomolecules. Similar constraints also limit the use of regulators when building synthetic circuits for engineering applications. Here, we mapped the promoter specificities of extracytoplasmic function (ECF)σ s as well as the specificity of their interaction with anti‐σ s. DNA synthesis was used to build 86 ECFσ s (two from every subgroup), their promoters, and 62 anti‐σ s identified from the genomes of diverse bacteria. A subset of 20σ s and promoters were found to be highly orthogonal to each other. This set can be increased by combining the −35 and −10 binding domains from different subgroups to build chimeras that target sequences unrepresented in any subgroup. The orthogonalσ s, anti‐σ s, and promoters were used to build synthetic genetic switches in Escherichia coli . This represents a genome‐scale resource of the properties of ECFσ s and a resource for synthetic biology, where this set of well‐characterized regulatory parts will enable the construction of sophisticated gene expression programs. Abstract : The interaction specificities of extracytoplasmic function (ECF) sigma (σ) factors with promoters and their negative regulators (anti‐σs) were mapped to identify non‐crossreacting parts. These orthogonal sets represent a synthetic biology toolbox of genetic switches. Synopsis: The interaction specificities of extracytoplasmic function (ECF) sigma (σ) factors with promoters and their negative regulators (anti‐σs) were mapped to identify non‐crossreacting parts. These orthogonal sets represent a synthetic biology toolbox of genetic switches. Part mining was applied to characterize 86 extracytoplasmic function (ECF) σs, their promoters, and 62 anti‐σs identified from the genomes of diverse bacteria. A subset of 20 σs and promoters were found to be highly orthogonal to each other and can be used to build non‐crossreacting switches in single cells. The N‐ and C‐terminal domains from σs from different subgroups can be recombined and recognize the corresponding chimeric promoter. These parts functioned off‐the‐shelf in an E. coli host with minimal re‐engineering and minimally affected host growth and gene expression.